Increased Asymmetry of Ecosystem Productivity Responses to Precipitation in Recent Two Decades - Licong Dai; Minqi Liang; Anping Chen; Guojiao Yang; Chuan Jin; Wenping Yuan; Zhongmin Hu (Geophysical Research Letters)
Abstract Projected increases in precipitation variability are expected to profoundly impact terrestrial vegetation productivity. Notably, the absolute change in ecosystem productivity to same amount of precipitation increase versus decrease may not be same. However, the generalization of this asymmetry, as well as its potential spatiotemporal variations, has rarely been assessed at the global scale. Here, we used multiple streams of satellite observation and found that asymmetry decreased along the humidity index gradient, indicating higher productivity pulse than decrease under dry climate conditions, and the asymmetry shifted from positive in dry areas to weakly negative in wet areas. Furthermore, the asymmetry increased significantly over the past two decades across most ecosystems. Climate change, particularly changes in precipitation, was the dominating factor behind the increasing global asymmetry over the last two decades. Our results suggest that increased precipitation variability may enhance vegetation productivity in arid regions, grassland, and shrub ecosystems, but could reduce productivity in forests.